Distribution and potential drivers of methane emissions from deep-sea environments in Haima cold seep areas - Li Tang; Jing-Chun Feng; Can-Rong Li; Xiao Chen; Hui Zhang; Si Zhang (Frontiers in Marine Science, 2025)
Introduction Tracing methane originating from deep-sea environments is essential for understanding the global methane budget. However, knowledge regarding the mechanisms governing methane transfer from deep-sea sediments to the water column in cold seep environments remains limited. This study aims to quantitatively investigate the distribution of methane and identify its controlling factors within the Haima cold seep areas. Methods A comprehensive analysis was conducted to investigate the distribution characteristics of methane and its potential drivers in both the water column and sediment porewaters within the Haima cold seep areas. Results The key findings are: (1) Haima cold seeps serve as a methane source to the atmosphere, with pronounced spatial heterogeneity in emission strength across the monitored regions. (2) The vertical distribution of methane is influenced by multiple environmental factors. Key factors in sediment porewaters include sediment depth, porosity, inorganic carbon (IC), chloride (Cl – ), and sulfate (SO 4 2– ), whereas silicate (SiO 3 2– ) and dissolved oxygen (DO) are primary regulators in the water column. (3) Sediments represent a significant methane source for bottom seawater, with methane consumption being more pronounced in seepage areas than in non-seepage areas. Discussion This study demonstrates that methane dynamics in the Haima cold seep are complex and driven by a combination of physical, chemical, and biological processes across the sediment–water interface. The identified key drivers underscore the importance of porewater geochemistry and water column biogeochemistry in controlling methane release. These findings significantly advance our understanding of methane transport in deep-sea seep systems and provide crucial insights for refining global methane flux estimates.

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.